Rancang Bangun Sistem Informasi Monitoring Dan Evaluasi Pelayanan Pemeliharaan Access Point Pada Regional Operation Center PT Telkom Indonesia Divisi Regional V - Wicaksono, Bayu Wikan; Supriyanto, Antok; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Monitoring and evaluation information system maintenance services access point is an information system that describes the flow of monitoring, recording, managing, and reporting services related to the maintenance of the access point. With the information system of monitoring and evaluation of care service access point at PT Telkom Regional Division 5 is expected to monitor and evaluate the care services for the managers of wireless ROC and accelerate supervisor Business Areas Telecommunications (Witel) to record data maintenance access point and monitoring open trouble wicket. With that quick decisions can be taken to the next step.Monitoring and evaluation information system maintenance service is web-based access point by using MySQL as a database for data availability are stable and free. On the menu of the app, create a new user, Witel master input, input master access point and open trouble ticket on the admin side ROC to open input on the supervisor handling Witel (SPV). for the input menu and all master data is a form that serves as an access point data management, as well Witel or handling, and there is a trouble ticket status table access point to view trouble ticket status information services required wireless manager ROC in monitoring maintenance services on Witel.